Perencanaan Instalasi Pengolahan Air Limbah Domestik Di Kampus Universitas Riau - Mutiara Zikron; Jecky Asmura; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The increase number of students at Riau University is 37,18% in 2017 which increased consumption of clean water that had an impact on increasing domestic wastewater in campus area. The technology use for wastewater treatment plants consists of equalization tanks and Anaerobic Baffle Reactor (ABR) tanks. The dimensions for the equalization building are 7 m long, 4 m wide, and 2,2 m high, while the dimensions for Anaerobic Baffle Reactor (ABR) is 19 m long, 9,5 m wide, and 1,5 m high.Keywords: Domestic Wastewater, Anaerobic Baffle Reactor